Land tenure and natural resource management: a comparative study of agrarian communities in Asia and Africa - Otsuka, Keijiro; Place, Frank (International Food Policy Research Institute, 2001)
The devastating environmental effects of deforestation and the exploitation of other natural resources in the developing world have been well documented, yet their impact on local communities has received far less attention. This volume fills this gap by looking at how land degradation and deforestation are being addressed at the local level, where households have experienced the reduction of farm size and the decline of natural resources. Through a comparison of Asia and Africa, Land Tenure and Natural Resource Management examines the evolution of land tenure institutions within diverse cultural, natural, and policy environments. Specific topics include the evolution of customary land tenure, the impacts of land tenure policies, and common property management. The editors conclude that the best strategy for managing land and forest resources lies in promoting the establishment of property rights and investment in the improvement of the natural resource base. Topics Include: Issues and Theoretical Framework; Quantitative Methodology; Agroforestry Management in Ghana; Agroforestry Management in Sumatra; Tree and Cropland Management in Malawi; Customary and Private Land Management in Uganda; Management of State Land and Privatization in Vietnam; Common Property Forest Management in the Hill Region of Nepal; Timber Forest Management in Nepal and Japan Toward New Paradigms of Land and Tree Resource Management.